Comparative study of prenatal development between myotis albescens (chiroptera: vespertilionidae) and eumops patagonicus (chiroptera: molossidae) : the chorionic vesicle and extraembryonic membranes considerations - Rodríguez, Florencia Evelyn (2018)
Fil: Rodríguez, Florencia Evelyn. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.